1963
DOI: 10.1139/y63-108
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Skeletal Muscle and Kidney During Nonshivering Thermogenesis in Cold-Acclimated Rats

Abstract: The oxygen consumption of the partly isolated leg muscles and of the kidney was measured in situ in cold-acclimated rats before and during exposure to cold or during noradrenaline infusion. All rats had been anesthetized with sodium barbital and those exposed to cold had been fully curarized to prevent muscle activity. During cold exposure and noradrenaline infusion oxygen consumption of the rats was approximately doubled, and the oxygen consumption of leg muscles was approximately doubled without increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1965
1965
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Acclimatization to winter conditions is associated with declines in the size of muscle tissue (red and white muscle fibers) in small rodents (Wiclder, 1981). This is important because muscle tissue is the site of shivering thennogenesis and a contributor to non-shivering thermogenesis (Jansky and Hart, 1963), Results of regressions of log muscle mass of the hind quarter versus log body mass indicated that changes in muscle had a proportionally greater effect on the overall changes in body mass for males compared with females.…”
Section: Resultsmentioning
confidence: 99%
“…Acclimatization to winter conditions is associated with declines in the size of muscle tissue (red and white muscle fibers) in small rodents (Wiclder, 1981). This is important because muscle tissue is the site of shivering thennogenesis and a contributor to non-shivering thermogenesis (Jansky and Hart, 1963), Results of regressions of log muscle mass of the hind quarter versus log body mass indicated that changes in muscle had a proportionally greater effect on the overall changes in body mass for males compared with females.…”
Section: Resultsmentioning
confidence: 99%
“…Skeletal muscle, due to its bulk, may be an important site of adrenergicinduced thermogenesis in human as well as in other animals. Adrenergic agonists have been demonstrated to increase oxygen consumption in skeletal muscle [110][111][112][113]. Although f-receptors in skeletal muscle are shown to be predominantly f2 [22][23][24][25], Challiss et al [1 14] recently compared the activity of various f-agonists and antagonists on the glycogen synthesis and lactate production in incubated muscle, and concluded that the 'A2' receptor in skeletal muscle is different from the classical fl2 receptor in smooth muscle.…”
Section: Brown Fat /1-receptormentioning
confidence: 99%
“…This may provide a mechanism for the facultative thermogenesis seen in resting skeletal muscle in response to NE demonstrated by us Clark et al 1995) and others (Jansky and Hart 1963;Grubb and Folk 1977;Richter et al 1982;Côté et al 1985;Shiota and Masumi 1988) in the constant flow perfused muscle preparation. However, there still remains uncertainty as to the identity of the tetrodotoxininsensitive sodium channel that NE, angiotensin II, and related vasoconstrictors indirectly activate and the mechanism(s) by which this activation occurs.…”
Section: Discussionmentioning
confidence: 60%
“…However, the exact function of UCP-3 is unknown, even though the involvement of this protein in skeletal muscle thermogenesis has been implied (Gong et al 1997;Larkin et al 1997). A third candidate mechanism for resting muscle thermogenesis relates to the observed stimulatory effects of adrenergic vasoconstrictors, particularly in perfused muscle preparations (Jansky and Hart 1963;Grubb and Folk 1977;Richter et al 1982;Côté et al 1985), where apart from an accompanying increase in perfusion pressure, little is known about the underlying mechanism. Studies from this laboratory have extended those original findings by showing, in the perfused rat hind limb preparation, that thermogenesis is stimulated by other vasoconstrictors including angiotensin II (AII) and vasopressin (Colquhoun et al 1988;Ye et al 1990).…”
Section: Introductionmentioning
confidence: 99%